Defamiliarization Through Myth: A Pastiche Reading of The Sword of Summer - Mukarramah, Linul Qalbi Ashlihatul; Kusuma, Agung Wiranata (Wanastra: Jurnal Bahasa dan Sastra, 2025)
This article explores how Rick Riordan applies the literary concept of pastiche and defamiliarization in his novel The Sword of Summer (2015). The study focuses on how elements of Norse mythology are blended with contemporary settings and characters to create a fresh and unfamiliar reading experience. Guided by Viktor Shklovsky’s theory of defamiliarization and Fredric Jameson’s idea of pastiche, the analysis reveals that the protagonist Magnus Chase and supporting character Samirah Al-Abbas are constructed through a fusion of ancient myth and modern identity. The appearance of mythological symbols such as the sword Sumarbrander, the fire giant Surt, and the reinterpretation of Valhalla as a high-tech hotel also represent a deliberate artistic choice that renews readers’ perceptions of traditional myth. Using a qualitative descriptive method, this study concludes that Riordan’s work challenges conventional depictions of heroes and mythology by encouraging readers to see both ancient narratives and present-day realities in unfamiliar ways. This blend of nostalgia and innovation not only attracts contemporary readers but also delivers a unique aesthetic experience through literary defamiliarization (Jameson, 1992; Shklovsky, 2015).